SISTEM AKUNTANSI PENGGAJIAN KARYAWAN DALAM MENINGKATKAN EFEKTIFITAS PENGENDALIAN INTERNAL PADA PT YUTAKA TRANS FABIO - Andriyaningsih, Hesty; Hutagaol, Layon Hocben (JURNAL MAHASISWA BINA INSANI, 2023)
The success of a company does not only lie in large profits but is also supported by success in terms of human resources. This can be seen from the important role of human resources, namely employees in the company, in maintaining the company's existence in carrying out existing business operations. The aim of the research is to find out the employee payroll accounting system at PT Yutaka Trans Fabio and to find out the internal controls related to the payroll accounting system at PT Yutaka Trans Fabio that have been implemented. This research method is descriptive qualitative. Data collection techniques include observation and interviews as primary data obtained directly from respondents including field coordinators, administration and accounting. Meanwhile, secondary data was obtained from various library materials such as books, journals and other documents related to this research. The results of the analysis and findings of this research are that the functions related to the payroll accounting system have not been fully implemented because there are still multiple functions carried out by the same person. Based on the research results, the author proposes to separate the functions related to the payroll accounting system at PT Yutaka Trans Fabio so that there is no duplication of functions by one person, such as the function of timekeeper and the function of making payroll and wages.